From Data to Knowledge: Systematic Review of Tools for Automatic Analysis of Molecular Dynamics Output - Baltrukevich, Hanna; Podlewska, Sabina (Frontiers in Pharmacology, 2022)
Increasing number of crystal structures available on one side, and boost of computational power available for computer-aided drug design tasks on the other, have made structure-based drug design tools being intensively used in the drug development pipelines. Docking and molecular dynamics simulations, key representatives of the structure-based approaches, provide detailed information about the potential interaction of a ligand with target receptor. However, at the same time, they require 3-dimensional structure of a protein and relatively high amount of computational resources. Nowadays, as both docking and molecular dynamics are much more extensively used, there amount of data being output of these procedures is also growing. Therefore, there are also more and more approaches, which facilitate the analysis and interpretation of results of structure-based tools. In the review, we will comprehensively summarize approaches for handling molecular dynamics simulations output. It will cover both statistical and machine-learning-based tools, as well as various form of depiction of molecular dynamics output